Demonstrasi Physical Exercise pada Lansia Hipertensi di Wilayah Kerja Puskesmas Tamalanrea Jaya Kota Makassar - Pujiningrum, Andi Rahmaniar Suciani; Majid, Abdul; Rini, Ita; Harisa, Akbar; Yodang, Yodang (Jurnal Abdimas Kesehatan (JAK), 2024)
The prevalence of hypertension in the world is still very high, according to the World Health Organization, one billion people in the world suffer from hypertension, two-thirds of whom are in developing countries with low and moderate incomes. The prevalence of hypertension in Indonesia continues to experience fluctuating changes in incidence rates, based on data from the South Sulawesi Provincial Health Office in 2020, according to Regency/City data, the highest prevalence of hypertension is in Makassar City with 290,247 cases. Tamalanrea Jaya Health Center is one of the Health Centers with a fairly high number of sufferers, namely 151 sufferers in 2022 with a population of 20,441 people. The purpose of this activity is to increase the knowledge and skills of the elderly regarding physical exercise. This activity was carried out on May 4, 2024 by conducting counseling and demonstration of physical exercise for the elderly. From this activity, 22 elderly people (88%) out of 25 respondents were able to do physical exercise independently. It is hoped that this activity can be a reference for the health center to develop a demonstration program for the application of physical exercise in daily life to improve the quality of life of the elderly.